Moving boredom from problem to opportunity: A psychoanalytic perspective on workplace boredom and identity in organizations. (September 2022) - Driver, Michaela
The study develops novel perspectives on workplace boredom by investigating how conscious and unconscious aspects of identity work drive responses to it. Based on a psychoanalytic, specifically Lacanian, analysis of 56 narratives in which individuals recount their experience with boredom at work, it explores why boredom is so often portrayed as dysfunctional. The study also examines why it is important to understand and strengthen boredom's more functional aspects. Specifically, the study advances the idea that boredom offers discursive resources to construct identities in more or less empowering ways with the potential for returning us to the creative possibilities inherent in each lived moment. Implications of this perspective are discussed.